PENGEMBANGAN VARIASI PERMAINAN BOLA BOTOL PELANGI PADA PEMBELAJARAN BOLA KECIL UNTUK SISWA KELAS IV SEKOLAH DASAR - Rachmat Nur Ichsan; I Nengah Sudjana; Fahrial Amiq (Gladi : Jurnal Ilmu Keolahragaan, 2018)
Variations in bottles rainbow ball game is a game played in groups by means of small ball and bottles targets by a wide range of colors in order to attract entusiastic students to play go and the game is developing a motor movement of students, train students to work together, to make a strategy, to good sportsmanship and to fair play so that the game can be used as teacher an alternative in learning small ball for the fourth grade students Elementary School. Research procedures used are referring to books Borg & Gall which has been modified in accordance Ardhana researchers from 10 steps to 7 steps. Test data analysis in the form of a percentage. Based on the analysis of data obtained by a small group test with subject 10 students it was obtained trial percentage of 87.97% and the percentage included in the creteria are eligible as well data analysis of test large group test with subject 30 students it was obtained a percentage of 88.70% and the percentage falls with in the creteria feasible, so we can say the product variations in bottles rainbow ball game is fit for use in the learning process.